The Strength Behavior and Desiccation Crack Development of Silty Clay Subjected to Wetting–Drying Cycles - Tu, Yiliang; Zhang, Rui; Zhong, Zuliang; Chai, Hejun (Frontiers in Earth Science, 2022)
It is commonly accepted that wetting-drying cycles have an effect on the soil strength behavior. Cracks development in soil is observed by many engineers during wetting-drying cycles, which may give a good explanation for the change of soil strength. A series of laboratory tests were conducted in this paper to investigate the desiccation cracks development and the strength change law for silty clay submitted to different number of wetting-drying cycles. The results show that the desiccation cracks at the end of drying process developed in two stages: stage of rapid growth and stage of steady state. The change law of soil strength is similar to the cracking that decreases quickly in the former stage and slowly in the latter stage, which indicates that the cracking in the soil is the main reason for strength reduction. Based on the assumption of an isotropic and linear elastic soil mass at rest earth pressure conditions, an equation for the depth of desiccation cracking after different number of wetting-drying cycles is obtained with soil mechanics for unsaturated soils. Finally, the applicability of the equation is verified compared with the experiment results.